PENGARUH BAURAN PEMASARAN UNTUK MENINGKATKAN KUNJUNGAN KONSUMEN PADA CAFE KOPI SOE DI TENGGILIS MEJOYO SURABAYA: Pemasaran - Ira Ade Nengtiyas (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2022)
Competition business in the cafe sector in Indonesia is very fast. Enjoying coffee is a cultural tradition for every society, especially in Indonesia, both in rural and urban areas. Consumers are now also selective in choosing cafes, and this causes cafe businesses to have to think of the right strategy in facing increasingly fierce competition. This study aims to determine the effect of the marketing mix on consumer visits at Cafe Kopi Soe in Tenggilis Mejoyo Surabaya. The method used is quantitative with sampling aimed at consumers of Café Kopi Soe with a total of 100 respondents, data collection using a questionnaire. The method of analysis in this study is multiple linear regression analysis, F test (simultaneous), T test, analysis of the coefficient of determination r2. Based on the results of the research data analysis, the Multiple Linear Regression Analysis shows that there is an influence between the X variable on the dependent variable Y. The largest value is 0.523. The F test shows that in this study it is 10.441 > F table of 2.10 and has a sig. 0.000 so that the X variable simultaneously affects the Y variable. The T test shows that the hypothesis is accepted t count > t table, it can be concluded that the dominant variable X has a t value of 3.997 > t table 1.984. Analysis of the coefficient of determination r2 shows that the results obtained R Square of 0.443. Then the conclusion of the study that all variables X have a significant effect on variable Y.